The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1126/science.1154122
|View full text |Cite
|
Sign up to set email alerts
|

Phytoplankton Calcification in a High-CO 2 World

Abstract: Ocean acidification in response to rising atmospheric CO2 partial pressures is widely expected to reduce calcification by marine organisms. From the mid-Mesozoic, coccolithophores have been major calcium carbonate producers in the world's oceans, today accounting for about a third of the total marine CaCO3 production. Here, we present laboratory evidence that calcification and net primary production in the coccolithophore species Emiliania huxleyi are significantly increased by high CO2 partial pressures. Fiel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

31
564
15
5

Year Published

2009
2009
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 726 publications
(615 citation statements)
references
References 32 publications
31
564
15
5
Order By: Relevance
“…The projected rate of change in ocean CO 2 chemistry leaves little time for organisms to evolve adaptations. While some species may be CO 2 -insensitive or able to adapt (e.g., Miller et al, 2009), the energetic costs of achieving net shell growth and preventing dissolution in conditions of aragonite under-saturation will likely have other impacts on overall growth rates, predation, metabolism or reproduction, as observed in organisms from other regions (e.g., Iglesias-Rodriguez et al, 2008;Fabry et al, 2008;Wood et al, 2008;Tunnicliffe et al, 2009).…”
Section: Ocean Acidificationmentioning
confidence: 99%
“…The projected rate of change in ocean CO 2 chemistry leaves little time for organisms to evolve adaptations. While some species may be CO 2 -insensitive or able to adapt (e.g., Miller et al, 2009), the energetic costs of achieving net shell growth and preventing dissolution in conditions of aragonite under-saturation will likely have other impacts on overall growth rates, predation, metabolism or reproduction, as observed in organisms from other regions (e.g., Iglesias-Rodriguez et al, 2008;Fabry et al, 2008;Wood et al, 2008;Tunnicliffe et al, 2009).…”
Section: Ocean Acidificationmentioning
confidence: 99%
“…Many studies focused on the effects of ocean acidification on coccolithophore (Riebesell et al, 2000;Feng et al, 2008;Iglesias-Rodriguez et al, 2008;De Bodt et al, 2010), but few considered the role of UVR in natural conditions (Gao et al, 2009). Our results indicate that reduced calcification in E. huxleyi made the cells more vulnerable when they are exposed to excessive light energy even without UVR considered, since reduced calcification led to downregualated photoprotective capability.…”
Section: Discussionmentioning
confidence: 99%
“…For example, a number of studies have investigated the consequences of reduced pH for calcifying phytoplankton (Table 1). Results by a number of laboratories suggest negative effects of higher CO 2 /lower pH on coccolithophore cultures (Riebesell et al, 2000(Riebesell et al, , 2007 but at least two studies indicate enhanced calcification under elevated CO 2 (Langer et al, 2006;Iglesias-Rodriguez et al, 2008). Ridgwell et al (2009) have suggested that some of these differences may be due to strain variations in the cultures used for these experiments; or there may be experimental design consequences resulting from the procedures used to adjust the pH .…”
Section: Ocean Acidification and Microbesmentioning
confidence: 99%